Immediate effect of selective neuromuscular electrical stimulation on the electromyographic activity of the vastus medialis oblique muscle - Denise DalAva Augusto; Paula Pinheiro Ventura; João Felipe de Souza Nogueira; Jamilson Simões Brasileiro (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p155 The Patellofemoral pain syndrome (PFPS) is described as an anterior or retropatellar knee pain in the absence of other associated diseases, and has often been associated with dysfunction of the vastus medialis oblique muscle (VMO). However, several studies have demonstrated the impossibility of selectively activating this muscle with exercises. The aim of the present study was to analyze the immediate effect of neuromuscular electrical stimulation of VMO muscle by means of monitoring the electromyographic activity of the vastus medialis oblique (VMO) and vastus lateralis (VL) muscles. Eighteen healthy women with a mean age of 23.2 years and mean BMI of 20 Kg/m2 were evaluated. The study protocol included electromyographic analysis of VMO and VL muscles, before and immediately after neuromuscular electrical stimulation of the VMO muscle. During the electromyographic analysis, the volunteers performed maximal voluntary isometric contraction in a 60° knee extension on an isokinetic dynamometer. "Russian current" apparatus was used for electrical stimulation. Results: The data analysis demonstrated a signifi cant increase in VMO activation intensity immediately after it had been electrically stimulated (p=0.0125), whereas VL activation intensity exhibited no signifi cant increase (p=0.924). Moreover, a significant increase in the VMO/VL ratio was also detected (p=0.048). In this study it was observed that electrical stimulation modifiedthe VMO/VL ratio, which suggests electrical stimulation has a benefi cial effect on VMO muscle strength.